Achievement Motivation and Entrepreneurial Interest of Barista as Training Graduates from Job Training Center - Desmira Wati; Wirdatul Aini (Universitas Negeri Padang, 2021)
The low interest in entrepreneurship of graduates of BLK Padang barista training, which is thought to be due to the low achievement of barista training graduates at BLK Padang, is the background of this research. Objectives (1) aim to excel (2) describe interest in entrepreneurship (3) describe the relationship between achievement motivation and entrepreneurial interest for barista trainer graduates. The approach in this study is a quantitative correlational type. In this study, the population was 64 people. The sampling technique used cluster random sampling, the 50% sample consisted of 32 people. The data collection technique is a questionnaire. The data analysis technique used theoretical theory, percentage and Spearman Rho. This study found that (1) achievement motivation was categorized as moderate. (2) the entrepreneurship interest of the barista training students is categorized as moderate. (3) There is a significant relationship between achievement motivation and the interest of graduates of barista training at BLK Padang.